Rice market integration in southern Sumatra, Indonesia (International Journal of Agricultural Research, Innovation and Technology, 2016)
This paper investigates rice market integration among five provinces in southern Sumatra using data from monthly retail rice markets during 2004-2009. The degree of integration was measured across provinces using vector error correction model. Result revealed that there is spatial market integration in southern Sumatra. Province of Bangka Belitung can make price adjustment more quickly compared to others provinces. In the long run period, rice price in Jambi province, Lampung province, and Bangka Belitung province became a reference price of rice in southern Sumatra. The study suggests policy recommendation for government to intervention this situation.Int. J. Agril. Res. Innov. & Tech. 5 (2): 1-6, December, 2015